Sekolah Asrama Islam dan Kecemasan Lingkungan: Studi Perbandingan - Dakkal Harahap; Baiduri; Yus Mochamad Cholily; Abdulkadir Rahardjanto; Rr Eko Susetyarini; Lud Waluyo; Atok Miftachul Hudha (Postgraduate, University of Mataram, 2026)
Environmental anxiety has increasingly been recognized as a significant psychological response to the global ecological crisis, particularly among adolescents within formal educational settings where climate change discourse is integrated into learning processes. As schools function as primary spaces for cognitive, emotional, and moral development, understanding how educational contexts shape students’ ecological concerns become essential. This study examines the impact of educational background on students’ environmental anxiety by comparing Islamic boarding schools (pesantren) and non-Islamic schools in South Tapanuli Regency. Employing a quantitative comparative design, data were collected from 60 students (30 pesantren and 30 non-pesantren) using an adapted Environmental Anxiety Scale. The analysis covered five dimensions: fear of ecological disasters, future anxiety, ecological guilt, ecological paralysis, and denial. Findings indicate that non-pesantren students reported significantly higher anxiety levels across all dimensions (p < 0.05), while also demonstrating stronger pro-environmental behavior (p < 0.01). In contrast, pesantren students exhibited lower anxiety levels, potentially reflecting the internalization of religious values and communal support as adaptive coping mechanisms. These findings suggest that educational background significantly influences adolescents’ emotional and behavioral responses to environmental challenges. The study contributes to policy discourse by emphasizing the integration of ecological literacy with spiritual and ethical reflection to foster ecological resilience and responsible behavior among young learners.